Homeopathic Treatment of Rheumatoid Arthritis: An Open, Observational Trial - Kundu, Nivedita; De, Mahadeb; Singh, Subhas; Michael, James; Nath, Arunava; Magotra, Nitin; Koley, Munmun; Saha, Subhranil (Homœopathic Links, 2019)
Background Rheumatological complaints including rheumatoid arthritis (RA) are frequently encountered conditions in homeopathy practice. On account of progressive destruction and disability of the joints, and troublesome side effects and dissatisfaction with the mainstream therapies, homeopathy remains one of the most sought-after therapies; however, it remained under-researched systematically. Aim of this trial was to evaluate the possible role of homeopathic treatment in RA by determining changes in severity of complaints and quality of life.Materials and Methods An open observational trial was performed on 50 patients suffering from RA (classified as per 2010 ACR/EULAR criteria) at National Institute of Homoeopathy, Kolkata and were assessed over 4 months of treatment. Disease Activity Score-28 (DAS28) and Rheumatoid Arthritis Disease Activity Index (RADAI) were used as the primary and secondary outcome measures respectively. Individualised medicines were prescribed on the basis of homeopathic principles.Results Six patients dropped out; 44 completed the trial. Intention-to-treat sample (n = 50) was analysed in the end. There were statistically significant reductions in both DAS28 score (6.8 ± 1.0 vs. 6.1 ± 1.2; mean reduction 0.7, 95% CI: 0.4–0.9, p < 0.001) and RADAI score (6.6 ± 1.8 vs. 5.2 ± 1.9; mean reduction 1.4, 95% CI: 1.0–1.9, p < 0.001) over 4 months of individualised homeopathic treatment.Conclusion Individualised homeopathic medicines seemed to produce promising treatment effects by reducing DAS28 and RADAI scores significantly over 4 months. Further randomised trials are warranted with enhanced methodological rigor (Trial registration: CTRI/2017/06/008848).
Keywords: rheumatoid arthritis; Disease Activity Score 28; Rheumatoid Arthritis Disease Activity Index; homeopathy